Instant photography - Jacobs, Lou. (New York : Lothrop, Lee & Shepard Co., 1976)
Explains how an instant camera works, describes techniques for taking photos, and presents projects for practice, fun, and profit.
Includes index.
Bibliography: p. 123.
Keywords: Artet boterore; Arti vizual-fotografia; Kamera polaroid; Polaroid Land camera -- Literatura per te rinj; Instant photography -- Juvenile literatureLiterature pre te rinj; Photography. -- Fotografia e castit; Artiste boterore; Fotografia-e castit-teknikat-metodat